CORRUPTION: A CRIME AGAINST HUMANITY - Mr.NiranjanMoharanaand Prof. Dr.N.C.Patnaik (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Modernization and Industrialization has given rise to the present day materialistic society. In this society, moral values, honesty, social good, spirituality have yielded place to individualism, competition, self good etc. This social order has thrown open a new challenge to the human society. Corruption is not a new phenomenon. Corruption is a potent violator of human rights, particularly the economic and social rights of individuals as well as those of the state. It not only undermines development and growth, it also inhibits efforts aimed at poverty eradication. Corruption has spread its effects to every sphere of the society. Corruption benefits the rich and it affects the poor. Unless it is checked, the government and people will have to pay a heavy price in the lower income, lower investment and lower development people.